Stability Analysis of Fractional-Order CHIKV Infection Model with Latency - Ramesh, P.; Sambath, M.; Balachandran, K. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we study the fractional order CHIKV infection model with latency. First, we establish the existence and uniqueness solutions of CHIKV model with latency. Next, we present the local and global stability of fractional order CHIKV model with latency. Finally, we produce some numerical solutions by using MATLAB software that supports the analytical results.